Aspek Leksikal Pada Lirik Lagu Seamin Tak Seiman Karya Mahen - Tahfidzul Hikam Nur; Intan Sari Ramdhani (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
The song is a variety of sounds that have a continuous rhythm so that many people enjoy the song as a hobby or just to accompany their daily life. The song is something that we hear the most, whenever and wherever we are. Nowadays, many songs are released at the same time, either because it is easy to create matching lyrics, harmonious rhythms, or because the song is a masterpiece that has free rules. Each song that is present certainly carries its own meaning and purpose. There needs to be a special study that discusses the lyrics of the song. In reviewing a song generally uses two aspects, namely the lexical and grammatical aspects. In this study, the writer analyzes a song lyric based on the lexical aspect which has two sub-discussions, namely repetition (repetition) and synonyms of equivalent words. The object of his research is a song by Mahen entitled